Role of human resource practices in absorptive capacity and R&D cooperation - Ipsita Roy (Friedrich Schiller University Jena, 2015)
While significant attention is given to the concept of absorptive capacity as a source of competitive advantage in firms, a major drawback exists in the way it is unidimensionally defined in micro-level analysis. The paper addresses this limitation and reconceptualizes absorptive capacity as a strategic human resource construct in firms, which in turn, provide important conditions for R&D cooperation and innovation. I begin by providing a "beyond-R&D" definition of absorptive capacity constituting employment practices and incentive-based compensation programs. Next, I exploit the relationship between these practices and heterogeneity in firms R&D cooperation and partner selection strategies distinguishing between different types of external collaboration partners- horizontal, institutional and consulting- based. Further, I examine the impact of such cooperative R&D on incremental product, process and radical innovation. Employing the IAB Establishment Panel Survey on about 1200 German innovation-based establishments during 2007-2011, findings demonstrate that adoption of employment practices positively affects R&D cooperation irrespective of the type of collaboration partner, while compensation programs positively affect only horizontal R&D cooperation. Significant differences in the patterns of research collaboration are found between manufacturing and service sector firms, with respect to importance of human resource management, educational structure of the workforce and internal R&D. Finally, cooperative R&D with research institutes and consulting firms are found to have significantly positive impact on the likelihood of coming up with incremental product, process and radical innovation, but the effect is relatively weak in case of horizontal R&D cooperation.
Keywords: J21; J24; J33; L20; M12; 330; absorptive capacity; compensation programs; employment practices; innovation; R&D cooperation; strategic human resource